Routine Hematologic and Biochemical Profiles in Term Premature Rupture of Membranes: A Retrospective Case-Control Study - Widiyanti, Septi; Fairus, Martini; Yuliawati, Yuliawati; Wibowo, Wahyu Dwi Ari (Journal of Applied Nursing and Health, 2026)
Background: Term premature rupture of membranes (PROM) is a common obstetric complication associated with increased risk of maternal and neonatal morbidity, primarily driven by inflammatory and infectious mechanisms. Although inflammatory pathways have been extensively studied, most evidence focuses on specific biomarkers such as C-reactive protein and cytokines. In contrast, routine hematologic and biochemical parameters—despite being widely available, inexpensive, and part of standard clinical practice—have not been consistently evaluated using PROM, particularly in low-resource settings such as Indonesia. Methods: This retrospective case-control study, reported according to STROBE guidelines, included 90 women (30 term PROM cases and 60 normal delivery controls) selected using systematic random sampling from medical records at Ahmad Yani Regional General Hospital, Indonesia. Inclusion and exclusion criteria were applied to minimize confounding. Eleven complete blood count (CBC) parameters were analyzed, including leukocytes, erythrocytes, hemoglobin, hematocrit, MCV, MCH, MCHC, platelets, RDW, MPV, and blood glucose. Laboratory measurements were performed using the Sysmex XN-550 hematology analyzer and the Pentra C400 automated chemistry analyzer. Data were analyzed using SPSS version 25. Group comparisons were conducted using the Mann–Whitney U test, and effect sizes were calculated using rank-biserial correlation. Results: Significant differences were observed in leukocyte count (p = 0.042), MCV (p = 0.016), MCH (p = 0.009), RDW (p = 0.023), and MPV (p = 0.036). Effect sizes ranged from small to moderate (r = 0.23–0.34), indicating limited clinical magnitude. Other parameters, including erythrocytes, hemoglobin, hematocrit, MCHC, platelets, and blood glucose, showed no significant differences (p > 0.05). Overall, the term PROM was associated with selective and subtle hematologic alterations. Conclusion: Term PROM is associated with mild and selective changes in routine hematologic parameters, particularly those related to inflammatory and erythropoietic activity. Blood glucose, the only biochemical parameter evaluated, remained comparable between groups. These findings suggest limited standalone diagnostic value, and complete blood count (CBC) parameters should be interpreted as supportive indicators within comprehensive obstetric assessment rather than independent diagnostic tools.